Massage Effleurage terhadap Adaptasi Kecemasan Primigravida - Purmata Putri, Masita; Jama, Fatma; Munir, Nur Wahyuni (Window of Nursing Journal, 2021)
Effleurage is a massage technique using the palms of the hands in a circular pattern of movements in several parts of the body or strokes along the back and extremities. This study aims to determine the effect of massage effleurage on the adaptation of the anxiety level of childbirth during the first active phase of primigravida at Masyita Maternity Hospital.The type of research used is experiment with pre-experimental design with one group prestest design approach because it will compare the situation before it is done with after treatment. The sample in this study were all 30 prigravida maternity respondents. The relationship test was carried out using the paired sample t test with a significance level (Î±) of 0.05.The results of the paired sample t test p = 0.000, which means that the p value is smaller than the value (Î±) 0.05, thus H0 is rejected and Ha is accepted. Interpretation of the effect of massage effleurage on the adaptation of the level of anxiety during labor during the active phase.With this research, it can be concluded that overcoming labor anxiety when 1 fae is active, can be done by doing non-pharmacological methods such as massage, for example by giving efflaurage massage, without having to take drugs. This research can increase knowledge, especially regarding the effect of massage effleurage on the adaptability of primigravida anxiety during the active phase. and can be used as a source of information, especially related to maternity nursing science.